Current best practice management of interstitial cystitis/bladder pain syndrome - Han, Esther (Ther Adv Urol, 2018)
INTRODUCTION: Over the last 100 years, the terminology and diagnosis criteria for interstitial cystitis have evolved. Many therapeutic options have changed, but others have endured. This article will review the idea of separating ‘classic’ Hunner lesion interstitial cystitis (HL IC) from non-Hunner lesion interstitial cystitis and bladder pain syndrome (N-HL IC/BPS) and their respective treatment algorithms. METHODS/RESULTS: A literature search was performed to identify articles and research on HL IC and N-HL IC/BPS including definitions, etiological theories, and treatments. This article is an overview of the existing literature. We also offer insight into how HL IC and N-HL IC/BPS are approached at our tertiary referral center. Additionally, American Urological Association guidelines have been integrated and newer treatment modalities and research will be introduced at the conclusion. CONCLUSION: The AUA guidelines have mapped out a stepwise fashion to treat IC/BPS; at our institution we separate patients with HL IC from those with N-HL IC/BPS prior to them entering a treatment pathway. We identify the rarer patient with HL as having classic ‘IC’; this cystoscopic finding is critical in guiding treatment. We believe HL IC is a distinct disease from N-HL IC/BPS and therapy should focus on the bladder. The vast majority of patients with N-HL IC/BPS need management of their pelvic floor muscles as the primary therapy, complemented by bladder-directed therapies as needed as well as a multidisciplinary team to manage a variety of other regional/systemic symptoms. Ongoing research into IC/BPS will help us better understand the pathophysiology and phenotypes of this complex disease while exciting and novel research studies are developing promising treatments.